Associations between students' perceptions of physical education teachers' interpersonal styles and students' wellness, knowledge, performance, and intentions to persist at physical activity: A self-determination theory approach. (November 2018) - Behzadnia, Behzad; Adachi, Paul J.C.; Deci, Edward L.; Mohammadzadeh, Hasan
Abstract: Objectives: Grounded in self-determination theory (SDT), the present study examined whether collegiate physical education (PE) teachers' autonomy support versus control would relate to college students' wellness, knowledge, performance, and intentions to persist at physical activity beyond the PE classes. The mediating roles of students' basic psychological need satisfaction and need frustration as well as their types of motivation (autonomous and controlled) were also modeled. Design: Cross-sectional study. Methods: One hundred and forty college students ( M age  = 21.69, SD  = 1.89) in PE classes completed questionnaires measuring their perceptions of PE teachers' autonomy support and control, as well as their own basic psychological need satisfaction and frustration and their autonomous and controlled motivation. The student outcomes were self-reports of the students' wellness (i.e., well-being and ill-being), teacher-administered tests of knowledge, teacher ratings of performance, and students' self-reports of intentions to persist at physical activity in the future. Results: Students' perceptions of teachers' autonomy support were positively associated with each of the positive student outcomes. Students' perceptions of teachers' control were related to students' well-being (negatively), knowledge (negatively), and ill-being (positively). Students' experiences of psychological need satisfaction were significantly positively related to their autonomous motivation and marginally to their controlled motivation. Their experiences of need frustration were related only positively to controlled motivation. As expected, path analyses showed that perceived autonomy support was positively related to the positive outcomes via need satisfaction and frustration and autonomous motivation, and that perceptions of teachers' control were related to students' ill-being (positively) and knowledge (negatively) through need frustration. Conclusions: Consistent with SDT, the findings suggest that teachers' autonomy support is important for student's psychological need satisfaction, type of motivation, and in turn the outcomes of well-being, knowledge, performance, and intention to persist in the domain of college PE programs. Practical and theoretical implications, along with limitations and future research suggestions are discussed. Highlights: Teachers' autonomy support was positively associated with college physical education students' positive outcomes. Need satisfaction, and autonomous motivation mediated the associations between autonomy support and wellness, knowledge, performance, and intention to continue. Teachers' controlling behaviors were negatively related to students' positive affect and knowledge, and positively associated with need frustration and negative affect. Need frustration mediated the positive association between controlling behaviors and negative affect.